Characterization of Evanescent Field Gas Sensor Structures Based on Silicon Photonics - Christian Ranacher; Cristina Consani; Natalie Vollert; Andreas Tortschanoff; Markus Bergmeister; Thomas Grille; Bernhard Jakoby (IEEE Photonics Journal, 2018)
Photonic sensors that operate in the mid-infrared spectral range are an emerging field for photonic microsystems. In this paper, we present a photonic gas sensor concept based on silicon waveguides using infrared evanescent field absorption. The waveguides were specifically designed for CO2 sensing at a wavelength of λ = 4.26μm as possible application for the proposed sensor platform. The waveguide cross section as well as the substructure were investigated using finite-element simulations and the devised structures were fabricated using mass fabrication processes exclusively. In order to evaluate the potential for long interaction path lengths using polysilicon strip waveguides, a study on the intrinsic losses of polysilicon waveguides was conducted. The lowest intrinsic damping that was obtained for polysilicon strip waveguides was 3.98 dB/cm. Furthermore, the sensing capability of the devised waveguides was tested with quantitative CO2 measurements down to a concentration of 500 ppm CO2. From the quantitative measurements, the evanescent field ratio was estimated and was in the range between η = 14%-16%.